Analysis of Endoscopic Pancreatic Function Test (ePFT)-Collected Pancreatic Fluid Proteins Precipitated Via Ultracentrifugation - Paulo, Joao A; Kadiyala, Vivek; Gaun, Aleksandr; Sauld, John F K; Ghoulidi, Ali; Banks, Peter A; Steen, Hanno; Conwell, Darwin L (JOP. Journal of the Pancreas, 2013)
Context We have shown previously that trichloroacetic acid precipitation is an effective method of protein extraction from pancreatic fluid for downstream biomarker discovery, compared to other common extraction methods tested. Objective We aim to assess the utility of ultracentrifugation as an alternative method of protein extraction from pancreatic fluid. Design Proteins extracted from trichloroacetic acid- and ultracentrifugation-precipitated pancreatic fluid were identified using mass spectrometry techniques (in-gel tryptic digestion followed by liquid chromatography-tandem mass spectrometry; GeLC-MS/MS). Data were analyzed using Proteome Discoverer and Scaffold 3. Setting This is a proteomic analysis experiment of endoscopically collected fluid in an academic center. Patients The study population included adult patients referred to the Center for Pancreatic Disease at Brigham and Women’s Hospital, Boston, MA, USA for the evaluation of abdominal pain and gastrointestinal symptoms. Interventions Secretin-stimulated pancreatic fluid was collected as standard of care for the evaluation of abdominal pain and gastrointestinal symptoms. Main outcome measures We compared proteins identified via standard trichloroacetic acid precipitation and this alternative ultracentrifugation strategy. Results A subset of pancreatic fluid proteins was identified via the ultracentrifugation method. Of these proteins, similar numbers were obtained from fully tryptic or semi-tryptic database searching. Proteins identified in the ultracentrifugation-precipitated samples included previously identified biomarker candidates of chronic pancreatitis. Conclusions This alternative ultracentrifugation strategy requires less time and fewer handling procedures than standard trichloroacetic acid precipitation, at the expense of higher sample volume. As such, this method is well suited for targeted assays (i.e., dot blotting or targeted mass spectrometry) if the protein of interest is among those readily identified by ultracentrifugation-promoted precipitation. Image: SDS-PAGE protein fractionation.